Palynostratigraphy, Paleoecology and Paleoclimatology of Early Pleistocene Based on Pollen Study of Pucangan Formation in Sangiran Area - Eko Yulianto; Woro Sri Sukapti; Ruly Setiawan (Pusat Survei Geologi, 2019)
A pollen study has been conducted on samples taken from Pucangan Formation in Sangiran area. This study aims to reconstruct palynostratigraphy and to reveal environmental dynamics along with the deposition of Pucangan Formation with an emphasis on the influence of high frequency volcanism to the vegetational landscape in the montane area. The co-occurrence of Phyllocladus hypophyllus and Podocarpus imbricatus indicates Plistocene age of samples, and their stratigraphic position overlied by Middle Pleistocene Kabuh Formation leads to a conclusion of Early Pleistocene. All samples are included in Monoporites annulatus Peak Zone and subdivided into three Peak Subzone i.e. Polypodisporites radiates, Psilotum nudum, Magnastriatites grandiosa, Cyathea sp. and Laevigatosporites sp. Concurrent Peak Subzone, Interval Subzone between two Peak Subzones i.e. Polypodisporites radiates, Psilotum nudum, Magnastriatites grandiosa, Cyathea sp., Laevigatosporites sp. Concurrent Peak Subzone and Casuarina sp. Peak Subzone. Along with the deposition of Pucangan Formation, savannah with sparse swamp, riparian and lowland forest spreaded out around particularly on lowland, while few mangrove forest grew on muddy sea-land interface environment and heterogenous montane forests occupied highland. During the deposition of stratigraphic profile, savannah got flourished on new emerged land due to regression. Frequent volcanic eruptions along with the deposition of the upper stratigraphic profile has destroyed heterogenous montane forest and led to the homogenous Casuarina junghuniana forest.Keywords: Palynology, Early Pleistocene, vegetational landscape, savannah, montane forest, regression, volcanism